Translanguaging and Code-Switching as Identity Construction for Generation Z on Instagram: A Sociolinguistic Study - Salsabila Intan Suci; Tri Setianingsih; Baiq Zuhrotun Nafisah (Journal of Pragmatics Research, 2026)
Instagram has evolved beyond a simple photo-sharing platform. For Generation Z in Indonesia, it functions as a key space where users actively shape their social identity and manage how they are perceived online. This research investigates the phenomenon of Translanguaging and code-switching in Instagram captions, framing it not merely as a bilingual habit but as a strategic communication tool that individuals deliberately use for self-presentation in digital contexts. Employing a qualitative document analysis method, this study examines ten captions taken from verified Indonesian public figures and influencers. The analysis draws on Poplack’s grammatical framework for identifying types of code-switching and Holmes’ sociolinguistic theory to interpret the social motives behind the practice. The findings reveal that intra-sentential switching is the most dominant pattern, accounting for 70% of all occurrences. This involves inserting English words or phrases into Indonesian sentence structures. The study identifies that this linguistic practice helps construct three primary digital personas: a Modern identity at 40%, a Global identity at 30%, and a Personal Branding image at 30%. While much of the existing literature has focused on spoken code-switching in face-to-face interactions, this research narrows the gap by examining code-switching in curated written discourse, specifically on Instagram captions. Although such texts are edited and asynchronous, they reveal deliberate identity positioning that contributes to the construction of the three digital personas identified in this study. This complements studies of spontaneous spoken interaction by showing how users strategically craft their bilingual persona for public audiences. The study concludes that for Generation Z, mixing Indonesian and English serves as a crucial form of social capital to navigate contemporary youth culture, which is heavily influenced by global trends and online status. These insights advance the understanding of bilingual practices and digital identity performance among Indonesian Generation Z.